Предмет: Алгебра, автор: kamillaisaeva

(sin^4 a - cos^4 a + cos^2a) / (2*(1-cosa))

Ответы

Автор ответа: Apofeoz
0
frac{sin^4 alpha -cos^4 alpha +cos2 alpha }{2(1-cos alpha )}=frac{sin^4 alpha -cos^4 alpha +cos^2 alpha-sin^2 alpha  }{2(1-cos alpha )}=\\=frac{sin^2 alpha (sin^2 alpha -1)+cos^2 alpha (1-cos^2  alpha )}{2(1-cos alpha )}=frac{sin^2 alpha (sin^2 alpha -1)+cos^2 alpha sin^2  alpha }{2(1-cos alpha )}=\\=frac{sin^2 alpha (sin^2 alpha -1+cos^2 alpha)}{2(1-cos alpha )}=frac{sin^2 alpha (1 -1)}{2(1-cos alpha )}=0.
Автор ответа: school123452
0
http://znanija.com/task/19479505 помогите
Похожие вопросы
Предмет: Алгебра, автор: sakorovm
Предмет: Литература, автор: Аноним